Seroprevalence of hepatitis E Virus among pregnant women attending Wad Madani Teaching Hospital, Sudan - Dawoud, Abakar Adam (Journal of Medical Biomedical and Applied Sciences, 2017)
Background: HEV is considered as one of liver diseases and other complications. The mortality rate may reach up to 20% in pregnant women with each passing trimester, making HEV infection the most severe hepatitis in pregnancy of all recognized hepatitis. Pregnancy appears to be a potential risk factor for viral replication and leads extreme low immune status of pregnant women. Hepatitis E in pregnancy is also associated with high rates of spontaneous abortion, intrauterine death, and preterm labour. Objectives: the objectives of this research are to estimate the Seroprevalence of HEV infection among pregnant women and detect IgG and IgM antibodies of HEV in pregnant women. Furthermore, association between HEV infection and disease determinants like age and different trimesters in pregnant women were investigated. Finally correlation between infection and (age, parity number, history of abortion, consumption of raw meat, and drinking of infiltrated water) and positive cases were also studied. Materials and methods: This was a descriptive cross-sectional hospital based study. Ninety serum samples randomly collected from pregnant women attended to Wad Madani hospital of obstetrics and gynecology were enrolled in the study. The age groups of the study population were 22 (24.4 %) aged less than 20 years, 41 (45.6 %) aged between 21-30 years and 27 (30.0 %) aged more than 40 years. also 30(33.3 %) had no history of abortion and 60 (66.7 %) had history of abortion.Results: 51 (56.7%) of participants diagnosed positive for anti-HEV IgG, while 39 (43.3%) gave negative results for anti-HEV IgG. On the other hand, 6 (6.7%) showed circulating anti-HEV IgM in sera of examined women, while 84 (93.3%) were negative for anti-HEV IgM. Liver function tests analysis revealed that only ALP and AST were affected by HEV infection (P value 0.020 and 0.026 respectively). According to age groups, there was significant relationship between Seroprevalence of anti-HEV IgG and anti-HEV IgM (P value 0.027). The highest prevalence noted among age group 21 â 30 years (45.6%) for IgG and less than 20 years (24.4%) for IgM. There is little relation between the positive results with biochemical findings. This study concluded that HEV was more prevalence in second (24%) and third trimester (59%) than first trimester (17%). The study recommended carrying out more studies and in large number of samples.